Symptoms and experiences of frailty in lung cancer patients with chemotherapy: A mixed-method approach - Duan, Liran; Cui, Huixia; Zhang, Wenlu; Wu, Shan (Frontiers in Oncology, 2022)
Objective: The aim of this study was to explore the symptoms and experiences of frailty in lung cancer patients treated with chemotherapy. Methods: Quantitative and qualitative research methods were implemented. A total of 302 patients aged > 18 years were recruited by convenience sampling method. Quantitative data were collected through the General Demographic Characteristics questionnaire, the Frailty Phenotype scale, the Cancer Fatigue Scale, the Hospital Anxiety and Depression Scale and the Pittsburgh Sleep Quality Index. Fourteen patients with a score of Frailty Phenotype scale ≥ 3 were drawn and their interviews were thematically analyzed. Results: The mean Frailty Phenotype score was (1.63 ± 1.35), suggesting that most of the patients were in pre-frailty conditions. A total of 64 (21.2%) patients were non-frail, 168 (55.6%) patients were pre-frail, 70 (23.2%) patients were frail. The mean CFS, HADS, scores, and Pittsburgh Sleep Quality Index scores were (26.96 ± 8.91), (15.41 ± 9.81), and (6.20 ± 4.39), respectively. Anxiety, fatigue, depression and poor sleep quality positively correlated with frailty. The qualitative research showed four themes. Theme 1: the most reported symptoms of frailty were physical symptoms and psychological symptoms. Physical symptoms included fatigue, low physical activity, weight loss and poor sleep quality. Psychological symptoms included anxiety, depression and low social activities. Theme 2: frailty was mainly related to lung cancer and chemotherapeutic drugs, which can cause decreased appetite, constipation and altered taste. Theme 3: patients used bad coping strategies to manage the symptoms of frailty. Theme 4: the social support of patients was weak, especially regarding emotional support. Conclusion: The most frequent symptoms reported by lung cancer patients treated with chemotherapy were anxiety, fatigue, depression, low physical activity and poor sleep quality. Patients also complained of bad coping strategies and weak support. Medical staff should strengthen the management of frailty, aiming at improving the quality of life in lung cancer patients treated with chemotherapy.